2018
DOI: 10.1002/bmc.4352
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomics research based on UHPLC‐ESI‐Q‐TOF‐MS coupled with metabolic pathway analysis: Treatment effects of stir‐frying Xanthii Fructus on allergic rhinitis in mice model

Abstract: Xanthii Fructus (XF), a well-known herb in traditional Chinese medicine, has been frequently used for the treatment of allergic rhinitis in the clinic. Its therapeutic metabolic mechanism, however, remains undetermined. In this work, a metabolomics research coupled with metabolic pathway analysis has been employed to screen out the potential mechanism in its effects on allergic rhinitis. Specifically, mouse serum samples containing XF were analyzed based on ultra-high performance liquid chromatography equipped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Xanthii Fructus, the ripe fruits of Xanthium sibiricum Patr., is a well-known herb used as traditional Chinese medicine [105]. OVA-sensitized Male BALB/C mice were orally treated with 1 g/kg of stir-fried Xanthii Fructus ethanol extract for 15 days.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Xanthii Fructus, the ripe fruits of Xanthium sibiricum Patr., is a well-known herb used as traditional Chinese medicine [105]. OVA-sensitized Male BALB/C mice were orally treated with 1 g/kg of stir-fried Xanthii Fructus ethanol extract for 15 days.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Twenty-seven potential biomarkers were discovered, mainly involved in metabolic pathways such as glycerophospholipid metabolism and branched-chain amino acid metabolism. 61 Wang, Y. et al found that gross saponins of Tribulus terrestris fruit can reverse middle cerebral artery occlusion-induced serum metabolic deviations by regulating multiple metabolic pathways. 62 Zhou, J. et al found that gastrointestinal injury was mainly related to vitamin B6 metabolism, phenylalanine metabolism, arachidonic acid metabolism, and taurine.…”
Section: Recent Advances and Applicationsmentioning
confidence: 99%
“…Traditional Chinese medicines (TCMs) are highly processed herbs. Many processing methods have been developed for processing herbs, such as stir‐frying (Zhuang et al, 2018), steaming (Zhu et al, 2016), wine‐sautéing (Huang et al, 2014), salt‐processing (Wu et al, 2022), among others. These methods are designed to meet certain clinical requirements.…”
Section: Introductionmentioning
confidence: 99%